The role of the professional social worker in disaster situations : In the case of the outbreak of the COVID-19 virus - Nunuan, Pinhathai (Journal of Multidisciplinary Academic Research and Development (JMARD), 2024)
The aims of this research are 1) to learn about the working models and roles of social workers during the crisis of the COVID-19 outbreak, 2) to present working guidelines of social workers during the crisis, which are appropriate to the changes, and 3) to provide lessons and suggestions for the work of sectors related to social work in Thailand. A mixed method research was applied by using a questionnaire as a survey research tool for the first group of informants, which were social workers working at the Social Development and Human Security Office in 76 provinces. Interview questions were used for the second group of informants, which were social workers in local administrative organizations, university academics who teach in the Faculty of Social Work, and social workers from private development organizations, totally 10 people analyzed data using content analysis. The research results were presented using descriptive statistics. The research results found that the working models during the crisis COVID-19 outbreak consisted of 1. Management by making merit and charity according to religious beliefs (philanthropy, charity, religious beliefs) 2. Management by using ingenious knowledge and local wisdom 3. Management based on the principles of rights, feminism and equality 4. Disaster management by the state, private sector and local community. Guidelines for working of social workers in crisis situations, propose for immediate relief measures and long-term prevention measures that specifies the operations in 3 phases including pre-pandemic phase, during the pandemic phase, and post-pandemic phase. Suggestions at the policy and practice levels include information management and integration of work between government agencies in each area with volunteer mechanisms in the community.